MEMANFAATKAN HASIL ASESMEN KOMPETENSI MINIMUM (AKM) UNTUK MENDESAIN MULTIMODAL LEARNING - Mustagfiroh Ali Imron (Madaris: Jurnal Guru Inovatif, 2022)
The method used in this discussion is a literature review from various sources. In general, this study aims to describe the multimodl learning design by utilizing the AKM results. The AKM result captures the real condition of student in mastering basic competence, namely reading literacy and numeracy literacy. The result can be used to improve the learning quality in classroom. To carry out teaching and learning in classroom, teachers need a certain approach. One being effective to improve learning outcomes is a multimodal approach that leads to multimodal learning. The multimodal learning design is constructed by utilizing the AKM results, intervention need students, basic, competent, and proficient. Meanwhile, multimodal learning design includes educational games, think-pair-share, case-based learning, personal journal entries, and multimodal research projects.